Evaluation of accessibility of people with reduced mobility: a study in the central region of Jaboticabal (Research, Society and Development, 2020)
To guarantee the right to come and go, as established in the Federal Constitution, the urban space must be built with accessibility to ensure the displacement of all. A large part of the Brazilian population has some difficulty in locomotion, whether it is related to physical condition that limits a person's movements, age or obesity. In the planning and design of urban spaces, many questions arise about the guarantee of accessibility. Thus, this work aimed to evaluate the public circulation spaces of the central region of Jaboticabal/SP regarding accessibility for people with reduced mobility. To perform the assessment, a technical accessibility assessment model was used regarding the existence of accessibility items, in accordance with NBR 9050/2004 and Decree No. 5,296 / 2004. The technical approach made it possible to measure concretely the routes that receive large circulation of people daily. The division of the studied paths in several segments promoted the identification of critical areas, and enables the adoption and prioritization of corrective actions, which will provide increased accessibility for people with reduced mobility.